Pengaruh Intensitas Penagihan Lapangan Dan Ketepatan Distribusi Terhadap Efektivitas Penagihan Piutang Melalui Sistem Monitoring Piutang Pada PT. Fuboru Indonesia Cabang Denpasar - Ni Putu Intan Maha Putri; Muspa Muspa; Maryam Nurdin (Movere Journal, 2026)
This study aims to analyze the effect of field collection intensity and distribution accuracy on accounts receivable collection effectiveness, with the receivables monitoring system as a mediating variable at PT Fuboru Indonesia, Denpasar Branch. This research adopts a quantitative approach using a survey method, in which data were collected through the distribution of questionnaires to active customers of PT Fuboru Indonesia, Denpasar Branch. The data analysis technique employed was Partial Least Squares–Structural Equation Modeling (PLS-SEM) using SmartPLS 4 software to examine both direct and indirect relationships among the research variables. The results indicate that (1) field collection intensity has a positive and significant effect on accounts receivable collection effectiveness at PT Fuboru Indonesia, Denpasar Branch; (2) distribution accuracy has a positive and significant effect on accounts receivable collection effectiveness; (3) field collection intensity has a positive and significant effect on accounts receivable collection effectiveness through the receivables monitoring system; (4) distribution accuracy has a positive and significant effect on accounts receivable collection effectiveness through the receivables monitoring system; (5) field collection intensity and distribution accuracy simultaneously have a positive and significant effect on accounts receivable collection effectiveness; (6) field collection intensity is the more dominant factor influencing accounts receivable collection effectiveness through the receivables monitoring system compared to distribution accuracy; and (7) the receivables monitoring system is also proven to have a significant effect and acts as a mediating variable that strengthens the influence of field collection intensity and distribution accuracy on accounts receivable collection effectiveness.